H.G. Wells : Classic Collection II - Wells, H. G. (Herbert George), 1866-1946; Illustrated by Edwards, Les (London Gollancz, 2011)
A second H.G. Wells omnibus collecting four classic SF tales, from the author of THE WAR OF THE WORLDS and THE TIME MACHINE
Include Picture
Keywords: Science fiction, English